VD_FINDINFO HC / 2017 / 956 vom 6. Oktober 2017 - VD Tribunal cantonal (2017)
SÛRETÉS, BAIL À LOYER, TRAVAUX DE CONSTRUCTION | 2 al. 2 CC, 259a CO, 260 al. 1 CO, 261 CPC, 264 al. 1 CPC, 74 CRF, 107 al. 1 let. f CPC (CH), 125 let. c CPC (CH)